“Sign Me Up”: a qualitative study of video observed therapy (VOT) for patients receiving expedited methadone take-homes during the COVID-19 pandemic - James B. Darnton; Elenore P. Bhatraju; Kristin Beima-Sofie; Alyssa Michaels; Kevin A. Hallgren; Sean Soth; Paul Grekin; Steve Woolworth; Judith I. Tsui (Addiction Science & Clinical Practice, 2023)
Abstract Background Federal and state regulations require frequent direct observation of methadone ingestion at an Opioid Treatment Program (OTP)—a requirement that creates barriers to patient access. Video observed therapy (VOT) may help to address public health and safety concerns of providing take-home medications while simultaneously reducing barriers to treatment access and long-term retention. Evaluating user experiences with VOT is important for understanding the acceptability of this strategy. Methods We conducted a qualitative evaluation of a clinical pilot program of VOT via smartphone that was rapidly implemented between April and August 2020 during the COVID-19 pandemic within three opioid treatment programs. In the program, selected patients submitted video recordings of themselves ingesting methadone take-home doses, which were asynchronously reviewed by their counselor. We recruited participating patients and counselors for semi-structured, individual interviews to explore their VOT experiences after program completion. Interviews were audio recorded and transcribed. Transcripts were analyzed using thematic analysis to identify key factors influencing acceptability and the effect of VOT on the treatment experience. Results We interviewed 12 of the 60 patients who participated in the clinical pilot and 3 of the 5 counselors. Overall, patients were enthusiastic about VOT, noting multiple benefits over traditional treatment experiences, including avoiding frequent travel to the clinic. Some noted how this allowed them to better meet recovery goals by avoiding a potentially triggering environment. Most appreciated having increased time to devote to other life priorities, including maintaining consistent employment. Participants described how VOT increased their autonomy, allowed them to keep treatment private, and normalized treatment to align with other medications that do not require in-person dosing. Participants did not describe major usability issues or privacy concerns with submitting videos. Some participants reported feeling disconnected from counselors while others felt more connected. Counselors felt some discomfort in their new role confirming medication ingestion but saw VOT as a useful tool for select patients. Conclusions VOT may be an acceptable tool to achieve equipoise between lowering barriers to treatment with methadone and protecting the health and safety of patients and their communities.